Latino images in film : stereotypes, subversion, resistance - Berg, Charles Ramírez, 1947- (Texas film and media studies series., 2002)
The bandido, the harlot, the male buffoon, the female clown, the Latin lover, and the dark lady - these have been the images of Latinos in US cinema for more than a century. This volume develops a theory of stereotyping that accounts for the persistence of such images in U.S. popular culture.